Treatment effects of dentofacial orthopedics followed by a multibracket appliance for Class II division 1 malocclusion: Učinek ortopedsko-ortodontske obravnave nepravilnosti razreda II, oddelek 1 - Fekonja, Anita; Špalj, Stjepan (Acta Medico-Biotechnica, 2026)
Purpose: The aim of this study was to evaluate the effects of a two-phase orthodontic treatment for Class II division 1 malocclusion and to compare the outcomes with the natural growth observed in untreated Class II subjects. Methods: The study group consisted of 27 patients (17 males and 10 females). Lateral cephalograms were evaluated before treatment (T0), after treatment with a functional orthodontic appliance during puberty (T1), and after treatment with a fixed appliance to achieve proper occlusion (T3). The mean age of patients before functional appliance therapy was 11.7 years (±0.7; Cervical Vertebral Maturation Stage (CVMS) 2–4). The effect of growth was assessed by comparing the results to untreated Class II cases in the control group. Results: Compared to untreated individuals, first-phase treatment with functional appliances significantly increased the effective mandibular length, reduced maxillo-mandibular sagittal skeletal discrepancy, improved the facial profile, and decreased overjet through the protrusion and proclination of maxillary incisors and the retrusion and retroclination of mandibular incisors (p ≤ 0.022). Dentofacial orthopedics did not significantly affect the vertical facial dimension. In the second phase, treatment with fixed appliances reduced the vertical facial dimension and reduced overjet, primarily through proclination and protrusion of the mandibular incisors (p ≤ 0.046). Conclusions: The first phase of Class II division 1 treatment produced greater effects than the second phase. In both phases, changes were predominantly dentoalveolar rather than skeletal.